KEMAMPUAN WHOLE CELL HELICOBACTER PYLORI DALAM MENGINDUKSI DEGRADASI KOLAGEN TIPE IV MELALUI PENINGKATAN AKTIVITAS MAKROFAG - Peristiowati, Yuly (STRADA : Jurnal Ilmiah Kesehatan, 2012)
Helicobacter pylori (H. pylori) an assosiation with acute myocardial infraction and cronic coronary disease. Bacteri cytotoxin can induce inflamatory of IL1-β and TNFα cytokine produce, and it can acitivated MMP-9 proteolotic enzyme, and it caused collogen degradation in plague atherosclerosis. This research aim to provit the whole cell H.pylori can induce the degradasi of collagen type IV by increase macrophage activity. It were seen from TNFα and IL1-β level use ELISA methode. Anova statistic analyse result show significan defferent (0,000) bettwen group control with macrophage induce whole cell H.pylori. Enzyme MMP-9 production detected with the gelatine zymography continued by western blotting with molecule weight 93 kDa. Collogen fragmentation result of molecule weight which fragment 61,2 kDa and 29 kDa. It concluded that whole cell H.Pylori can induce the degradation of collagen type IV, by increase macrophageag activity. So, the result of this research can support the patomekanism myocardial infract disease.